THE ASSOCIATION OF MYASTHENIA GRAVIS AND IMMUNE-MEDIATED MYOPATHIES: The association of de novo MG and IIM - Micic, Aleksandar; Viric, Vanja; Božović, Ivo; Momcilovic, Nikola; Ivana (Medical Research, 2023)
Introduction/Aim: Myasthenia gravis (MG) is a chronic autoimmune disease of the neuromuscular junction, characterized by muscle weakness and fatigability. Idiopathic inflammatory myopathies (IIM) are an immune-mediated group of diseases characterized by progressive painful proximal weakness of the extremities. The coexistence of these two diseases is extremely rare and so far, only about fifty cases have been reported world-wide. The aim of this study was to analyze the frequency of coexistence of IIM and patients with de novo MG.Material and Methods: The study is retrospective in nature and was conducted at the Clinic for Neurology, University Clinical Center of Serbia. The study included 97 patients diagnosed with myasthenia gravis between January 1, 2014, and December 31, 2018.Results: The average age of the MG patients was 54.1±18.9 years. At the time of diagnosis, 19 (19.6%) had at least one of the anamnestic data observed as a potential indicator for the existence of immune-mediated myopathy. Finally, in one patient he clinically presented the existence of generalized seropositive (anti-AchR positive) myasthenia gravis associated with the existence of a diagnosis of antisynthetase syndrome. In addition, main characteristics of a patient with the combined appearance of de novo MG and antisynthetase syndrome are presented.Conclusion: Although the simultaneous occurrence of MG and IIM is a very rare phenomenon, it is necessary to think about the possibility of the combined occurrence of these two autoimmune diseases, with the aim of early recognition and adequate treatment, and thus a better prognosis of both diseases.
Keywords: Myasthenia gravis; inflammatory myopathy; antisynthetase syndrome; coexistence